Shaykh Yusuf al-Makassari: Political Exile, Religious Authority, and Historical Legacy in South Africa - Alkhairi; Erasiah; Nelmawarni; Johan Septian Putra (Journal of Philology and Historical Review, 2025)
The history of Islam in Southeast Asia and Africa cannot be disentangled from the dynamics of migration, colonialism, and spiritual resistance to subjugation. Shaykh Yusuf al-Makassari (1626–1699 CE) a nobleman, Islamic scholar, Sufi master, and anti-colonial resistance fighter from Makassar, South Sulawesi represents one of the most consequential transnational figures in the global history of Islam. This study aims to reconstruct the historical trajectory of Shaykh Yusuf al-Makassari, from his political captivity under the Dutch East India Company (VOC) to his enduring role as a foundational figure of Islam in South Africa. Employing a library research methodology integrated with the historical research method, comprising heuristics, source criticism, interpretation, and historiography. This study systematically analyzes primary and secondary sources pertaining to Shaykh Yusuf's life, exile, and legacy. The findings reveal that despite being forcibly exiled to Ceylon (1684) and subsequently to the Cape of Good Hope (1694), Shaykh Yusuf succeeded in establishing the first consolidated Muslim community in South Africa through the clandestine transmission of Khalwatiyya Sufi teachings, thereby earning recognition as the "Father of Islam in South Africa" — a legacy later celebrated by Nelson Mandela as the foundational inspiration of South Africa's anti-apartheid and anti-colonial struggle.